Chaucer and Italian textuality - Clarke, Kenneth Patrick, 1977- (Oxford : Oxford University Press, 2011)
K.P. Clarke explores how Chaucer's work was affected by the tradition of commentary on or glossing of vernacular poetry, and how this context affected the layout and therefore the reading of texts within specific manuscripts. He seeks to understand Chaucer's Italian sources, as they were read by Chaucer himself.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chaucer, Geoffrey, -- d. 1400 -- Criticism and interpretation; Boccaccio, Giovanni, -- 1313-1375 -- Influence; English literature -- Early modern, 1500-1700 -- Italian influences; Italian literature -- Appreciation -- England -- History -- To 1500.